Pernambuco dos oitocentos: um narrativa sobre os escravizados nos inventários post-mortem do casal Francisco de Paula Cavalcanti de Albuquerque e Maria Rita de Albuquerque Mello: 1814 a 1822. - Coelho, Maria de Fátima Dias (2020)
This report concerns the historical research carried out at the Archaeological, Historical and Geographic Institute of Pernambuco - IAHGP - in November 2019, on the post - mortem inventories belonging to the couple Francisco de Paula Cavalcanti de Albuquerque and Maria Rita de Albuquerque Mello, in the years from 1814 to 1822, in the lands of Pernambuco that allowed the literary-historical production of the book “Heritage in Pernambuco of the nineteenth century: a narrative about the slaves of Francisco de Paula Cavalcanti de Albuquerque and Maria Rita Albuquerque de Mello”. The course of this work is methodologically traced as an empirical-inductive research, in which a piece of Pernambuco's slave-making history can be told in its historical aspects, through the inventories of that couple. This research can also be defined as a case study, since the object of study is a historical reality that can reveal some important aspects about that historical period. Another important methodological aspect is characterized by the documentary survey of inventories from 1814 to 1822, which make up the IAHGP collection. The objective of the research was to unveil a section of the slave culture in Pernambuco, through these characters and their relationship with their slaves, describing and narrating the historicity and the period and a cut out experience, namely: the post mortem inventories belonging to the couple Francisco de Paula Cavalcanti de Albuquerque and Maria Rita de Albuquerque Mello, in the years 1814 to 1822, in the lands of Pernambuco. From this historical plunge, it is concluded that the collections of inventories can enlighten us and allow interpretations of the historicity of that historical period, unraveling, through them, social and economic contexts.